Capacitación técnico-pedagógico en el aula taller de la Universidad Técnica de Cotopaxi sobre el déficit de atención, dirigido a las estudiantes de la carrera de educación parvularia, de la ciudad de Latacunga, provincia de Cotopaxi en el año 2012-2013 - Molina Segovia, Andrea Soledad (2014)
The presented investigation left from the necessity of improving the educational system, the same one that has tried to overcome in class classrooms the problem that contains the deficit of attention, this has not allowed the teachers to achieve in the kindergartens the integral development. The deficit of attention became a threat from the educational point of view, preventing to elevate the knowledge presenting inconveniences that were reflected with passing of the time in levels superiors of studies. The acquisition of more knowledge is necessary for the improvement of the quality of the education to the students of the career of Parvularia, it has been verified necessities that should be included in the curricular mesh to allow the training and power to face the inconveniences presented in the class classrooms, the deficit of attention it not only affected in those who have that problem but it involved to the environment giving as a result that the learning is smaller.